Setting the Phosphorus Boundaries for Greek Natural Shallow and Deep Lakes for Water Framework Directive Compliance - I. Kagalou; C. Ntislidou; D. Latinopoulos; Kemitzoglou, D.; Tsiaoussi, V.; D. Bobori (2021)
Kagalou I, C. Ntislidou, D. Latinopoulos, D. Kemitzoglou, V. Tsiaoussi, and DC Bobori. 2021. Setting the Phosphorus Boundaries for Greek Natural Shallow and Deep Lakes for Water Framework Directive Compliance. Water 13(5):739. https://doi.org/10.3390/w13050739